Edukasi Penggunaan Obat dan Suplemen untuk Pencegahan Non-Communicable Diseases (NCDs) pada Pekerja Imigran Indonesia di Sanggar Bimbingan Sungai Mulia, Kuala Lumpur, Malaysia - Heroweti, Junvidya; Budiarti, Aqnes; Inayati, Dian; Ikhsan, Muhammad (Journal of Dedicators Community, 2024)
The health of Indonesian immigrants working in Malaysia is a concern due to difficulties in obtaining health and medical facilities. Non-Communicable Diseases (NCDs) are increasing rapidly in Indonesia and Malaysia due to unhealthy lifestyles and eating patterns. The aim of this service is to increase awareness of Indonesian immigrants in Malaysia, especially at Sanggar Guidance (SB) Sungai Mulia 5, Gombak, Kuala Lumpur, Malaysia. This service begins with situation analysis, health outreach, assistance with medication use and evaluation of understanding regarding NCDs. Based on the results of health outreach and medical check-ups, it is known that as many as 70% of immigrants experience high blood pressure; 60% experienced high blood sugar; 30% experienced high uric acid and 57.5% experienced hypercholesterolemia. The results of the evaluation of the use of supplements and herbs to prevent NCDs showed that more than 70% of participants had an understanding of metabolic diseases, symptoms of NCDs, lifestyle improvements, processing and use of herbs, use of multivitamins, use of medication from a doctor (if they had received therapy). This activity can support information on health status and increase understanding regarding the use of medicines and herbs among Indonesian immigrants in Malaysia.